2004
DOI: 10.1111/j.1469-8137.2004.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

A gene encoding a polygalacturonase‐inhibiting protein (PGIP) shows developmental regulation and pathogen‐induced expression in strawberry

Abstract: Summary• Polygalacturonase-inhibiting proteins (PGIPs) have been demonstrated to play a role in host defence in several plants.• The PGIP now cloned from strawberry ( Fragaria × ananassa ) showed a high degree of homology to other fruit PGIPs. The gene expression of strawberry PGIP was monitored in healthy leaves, flowers and fruit at different maturity stages. PGIP transcript levels were also analysed following fruit inoculation with the fungal pathogen Botrytis cinerea in strawberry cultivars displaying vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 46 publications
2
40
0
2
Order By: Relevance
“…These results are similar to the expression pattern of the BnPGIPs (Li et al, 2003) and BcPGIP (Ahsan et al, 2005). The expression of RsPGIP1 is also observed by mechanical wounding as reported in PGIPs from Arabidopsis (Li et al, 2003), Chinese cabbage (Ahsan et al, 2005), strawberry (Mehli et al, 2004), and bean (Devoto et al, 1998). Mechanical wounding is generally generated in the infection site where defense-related genes may be active against pathogens (Schenk et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results are similar to the expression pattern of the BnPGIPs (Li et al, 2003) and BcPGIP (Ahsan et al, 2005). The expression of RsPGIP1 is also observed by mechanical wounding as reported in PGIPs from Arabidopsis (Li et al, 2003), Chinese cabbage (Ahsan et al, 2005), strawberry (Mehli et al, 2004), and bean (Devoto et al, 1998). Mechanical wounding is generally generated in the infection site where defense-related genes may be active against pathogens (Schenk et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
“…A variety of PGIP genes have been cloned from 103 plant species ; NCBI gene bank). Recently, PGIP genes in rape, rice, strawberries and Chinese cabbage have been identified (Ahsan et al, 2005;Mehli et al, 2004). Most PGIP genes are composed of multi-gene families clustered in a particular chromosomal region.…”
Section: Introductionmentioning
confidence: 99%
“…The Colletotrichum species are known to produce enzymes that degrade carbohydrates and thus dissolve plant cell walls (e.g., polygalacturonases, pectin lyases and proteases) and hydrolyze fruit cuticles (Wharton & Diéguez-Uribeondo, 2004). In a response, several plants have evolved inhibitor proteins (PGIPs) that specifically recognise and inhibit fungal polygalacturonases (Mehli et al, 2004). Recently, a new report concerning the reduction of Colletotrichum acutatum infection by a polygalacturonase inhibitor protein extracted from apple, has been provided (Gregori et al, 2008).…”
Section: Colletotrichum Spp As Pathogenic Fungi Of Olea Europaea Lmentioning
confidence: 99%
“…In the strawberry plant, one study found clear induction of PGIP due to infection with B. cinerea, whereas wounding failed to impact the transcription level [80]. In the potato plant, PGIP accumulation increased fi ve-fold after infection with Phytophthora infestans [81].…”
Section: Pgpgip (Polygalacturonase Inhibiting Protein)mentioning
confidence: 99%